ORIENTATION OF SERVICE LEVEL AGREEMENT (SLA) RESOURCE ALLOCATION IN ADAPTIVE CLOUD MONITORING SYSTEM - K Suneel Kumar, Dr.Dhanraj Verma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this latest period, there had been developing attentiveness in addressing the over- provisioning and under-provisioning of elastic cloud resources due to the Service Level Agreement (SLA) contravention issue. Latest analyses have described that federated cloud services serve as a best elastic cloud model than a single provider model. An important issue with a federated cloud is interoperability among multiple cloud service providers. In this paper Orientation of Service Level Agreement (SLA) resource allocation in adaptive cloud monitoring system is implemented. In this initially, data center will take input data from VM resource. Next cloudlet scheduler will schedule the data and VM scheduler will take the scheduled data from cloudlet scheduler and schedule according to the VM scheduler. Now the data is scheduled according to the given process then host will update the process to cloudlet. Now unity function is performed to the obtained data. At last process is migrated to get effective outcome. From results it can observe that it improves the security, reduces the cost and complexity.